Divergent perspectives among medical and non-medical personnel implications in the context of the Covid-19 pandemic. - Moraru Liviu; Bodea Reka; Voidäzan Toader Septimiu; Badau Dana; Moraru Raluca (Balneo & PRM Research Journal, 2025)
: In Romania, an increased number of infections with the new coronavirus have been reported, which has led to the deterioration of the state medical system, already facing multiple problems due to outdated infrastructure, lack of equipment and lack of personnel. Lack of trust in the Romanian healthcare system and the absence of basic health education programs are considered among the main causes that contributed to the skepticism with which Romanian citizens viewed the pandemic situation, complicating the management of the COVID‐19 pan‐demic. Objectives: The aim of study was determining the differences in perspectives on COVID‐19 between individuals with and without medical training and assessing their potential impact on pandemic management. A cross‐sectional study was conducted using a questionnaire, that was administered to a sample of 253 individuals from June 2022 until March 2023 and was distributed online through the Google Forms platform. The data obtained from participantsʹ questionnaire responses were entered into the Microsoft Office Excel platform and then statistically processed using the Statistical Package for Social Sciences (SPSS) software. Frequency tables were employed, and for qualitative data, chisquare tests were applied. The statisti‐cal significance was established by referencing a ʺpʺ value of 0.05, with values below this threshold considered statistically significant. In regards to respondentsʹ perception about the existence of the virus or the origin of the pandemic,  25.7% of them believed that the virus was artificially created and accidentally released, while 15% believed that it was released by malevolent entities. The burden of restrictions was felt most among those without medical training at a rate of 17.3%. Of those studying/working in the medical field, 57.1% con‐sidered that mandatory vaccination was the only solution to overcome the pandemic. Of those without medical education, 56.7% considered compulsory vaccination as a form of abuse. Those who study/work in the field believe that it is absolutely necessary to implement health education programs in schools. Indi‐viduals in rural areas were more inclined to deny the existence of the SARS‐CoV‐2 virus. Moreover, denial rates were elevated among those with lower educational attainment. This cohort demonstrated a predisposition towards a ʺcounter‐systemʺ mindset. Skepticism regarding Covid vaccines and the healthcare system was more pronounced within this demographic. Respondents with medical education exhibit heightened trust in measures enforced by authorities, official statistics, and vaccination campaigns.
Keywords: : Covid 19; SARS‐CoV‐2; healthcare; questionnaire